2022
DOI: 10.3390/medicina58050562
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on the Quality of Life of IBD Patients

Abstract: Background and Objectives: The COVID-19 pandemic has had a considerable impact on inflammatory bowel disease (IBD) patients by limiting their access to medical services due to restrictions and the reorganization of the healthcare systems, which affects their quality of life (QoL). We aimed to assess the impact of the COVID-19 pandemic on the QoL of patients with IBD. Materials and Methods: We conducted a descriptive observational study, which included 90 adult patients diagnosed with IBD. The study sample cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The fear of COVID-19 and its association with other psychological and health outcomes in patients with IBD has been widely investigated. Emotional stress is a compounding factor for the symptoms of patients with IBD and could influence the severity of the disease [ 36 ]. Deterioration of health-related quality control in patients with PIBD was reported in the period during and after the quarantine for COVID-19, leading to an increased number of patients with active disease, as well as to reduced disease control [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fear of COVID-19 and its association with other psychological and health outcomes in patients with IBD has been widely investigated. Emotional stress is a compounding factor for the symptoms of patients with IBD and could influence the severity of the disease [ 36 ]. Deterioration of health-related quality control in patients with PIBD was reported in the period during and after the quarantine for COVID-19, leading to an increased number of patients with active disease, as well as to reduced disease control [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from empirical studies are, however, controversial. Some investigations found that, during the stay-at-home period, up to one third of IBD patients reported poor HRQoL and moderate to severe anxiety and depressive symptoms [39][40][41][42][43] whereas, in contrast, other investigations showed that disability and HRQoL were unaffected by the COVID-19 pandemic [44][45][46]. The conclusions of those previous studies are, however, limited by the lack of a control for DA.…”
Section: Introductionmentioning
confidence: 96%
“…Patient-reported outcomes (PROs) measure the patient's experience of the disease and impact of treatment without the burden of extensive medical evaluations, leading to improvement in the patient's quality of life. In recent times, the attainment of living remission, which includes normalized health-related quality of life and the elimination of disability, has emerged as a therapeutic target and disease activity index [11,12].…”
Section: Introductionmentioning
confidence: 99%